On Multivalued Hybrid Contractions with Applications - Monairah Alansari; Shehu Shagari Mohammed; Akbar Azam; Nawab Hussain (Journal of Function Spaces)
Recently, a notion of b-hybrid contraction for single-valued mappings in the framework of b-metric spaces which unify and improve several significant existing results in the corresponding literature was introduced. This paper presents a multivalued generalization for such contraction. Moreover, one of our obtained results is applied to analyze some solvability conditions of Fredholm-type integral inclusions. Nontrivial examples are also provided to support the assertions of our theorems.